Consequence of Fibonacci quasiperiodic sequences in 1-D photonic crystal refractive index sensor for the blood plasma and cancer cells detections - Singh B.K.; Rajput P.S.; Dikshit A.K.; Pandey P.C.; Bambole V. (My University, 2025)
We present the consequences of different Fibonacci quasiperiodic sequences on the sensing performance of a one-dimensional (1D) photonic crystal (PC) based sensor to detect the blood plasma and cancer cells. We demonstrate that the sensitivity and figure of merit (FOM) of the sensor can be modulated, respectively, from 427.5 nm/RIU to 530 nm/RIU and from 162.5 RIU−1 to 2983.33 RIU−1 by utilizing the pertinent sensor structures with Fibonacci generation and structural parameters for the analyte refractive index from 1.31 to 1.41. We have also shown that the operational sensing wavelengths and sensitivity can be changed significantly by introducing the different Fibonacci sequences in the proposed sensor. The sensing peaks separation, FWHM, and sensitivity can also be tuned by changing the analyte and PC stacked layers' thicknesses. We also introduce the sensing performances for the Blood plasma and Cancer cells detection using the proposed Fibonacci quasiperiodic PC sensor. We observe that the maximum sensitivities and FOM of the proposed sensor are 552.5 nm/RIU and 2986.93 RIU−1 for cancer cells and 553.55 nm/RIU and 2214.21 RIU−1 for blood plasma, respectively. The proposed structure reveals the tunable sensing performances and stimulates the fabrication interest. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.